Empowering lower limbs exoskeletons: state-of-the-art. Issue 11 (15th August 2018) - Viteckova, Slavka; Kutilek, Patrik; de Boisboissel, Gérard; Krupicka, Radim; Galajdova, Alena; Kauler, Jan; Lhotska, Lenka; Szabo, Zoltan
SUMMARY: Given the advanced breakthroughs in the field of supportive robotic technologies, interest in the integration of the human body and a robot into a single system has rapidly increased. The aim of this work is to provide an overview of empowering lower limbs exoskeletons. Along with lower exoskeleton limbs, their unique design concepts, operator–exoskeleton interactions and control strategies are described. Although many problems have been solved in recent development, many challenges remain. Especially in the context of infantry soldiers, fire fighters and rescuers, the challenges of empowering exoskeletons are discussed, and improvements are outlined and described. This study is not only a summary of the current state, but also points to weaknesses of empowering lower limbs exoskeletons and outlines possible improvements.